2021
DOI: 10.3390/ijms222111864
|View full text |Cite
|
Sign up to set email alerts
|

The Fibrotic Effects of TMAO on Human Renal Fibroblasts Is Mediated by NLRP3, Caspase-1 and the PERK/Akt/mTOR Pathway

Abstract: Trimethylamine N-oxide (TMAO), a product of gut microbiota metabolism, has previously been shown to be implicated in chronic kidney disease. A high TMAO-containing diet has been found to cause tubulointerstitial renal fibrosis in mice. However, today there are no data linking specific molecular pathways with the effect of TMAO on human renal fibrosis. The aim of this study was to investigate the fibrotic effects of TMAO on renal fibroblasts and to elucidate the molecular pathways involved. We found that TMAO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 74 publications
(95 reference statements)
4
25
0
4
Order By: Relevance
“…The aberrant activation and proliferation of fibroblasts are thought to be a key cause of renal fibrosis. Evidence exists that the inhibition of PERK-Akt-mTOR-NLRP3 signaling inhibits the renal fibroblast activation and fibroblast proliferation [ 81 ]. In addition to this, NF- κ B translocation and ROS production in renal thylakoid cells exposed to angiotensin II activate NLRP3 inflammasomes, which can lead to glomerular fibrosis [ 82 ].…”
Section: The Role Of the Abnormal Metabolite-induced Nlrp3 Inflammaso...mentioning
confidence: 99%
“…The aberrant activation and proliferation of fibroblasts are thought to be a key cause of renal fibrosis. Evidence exists that the inhibition of PERK-Akt-mTOR-NLRP3 signaling inhibits the renal fibroblast activation and fibroblast proliferation [ 81 ]. In addition to this, NF- κ B translocation and ROS production in renal thylakoid cells exposed to angiotensin II activate NLRP3 inflammasomes, which can lead to glomerular fibrosis [ 82 ].…”
Section: The Role Of the Abnormal Metabolite-induced Nlrp3 Inflammaso...mentioning
confidence: 99%
“…NLRP3-mediated damage and necrosis of ECs were also found in diseases which are relevant to vasculopathy [ 14 , 15 ]. NLRP3 also shows ability to activate fibroblasts, the most important cellular component of fibrosis, in chronic inflammatory diseases, inducing cell activation and differentiation [ 16 , 17 ].…”
Section: Overview Of Nlrp3mentioning
confidence: 99%
“…It consists of tubular cells, peritubular endothelium of the capillaries, extracellular matrix, pericytes, fibroblasts and immune cells [ 16 ]. The role of TMAO in the renal tubulointerstitium has also been a subject of investigation [ 5 , 17 ]. Increased TMAO in a CKD mice model was associated with tubulointerstitial fibrosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased TMAO in a CKD mice model was associated with tubulointerstitial fibrosis [ 5 ]. We have previously shown that TMAO induces proliferation of human renal fibroblasts and collagen production via the Akt/mTOR pathway [ 17 ]. Tubulointerstitial fibrosis and inflammation lead, in the context of CKD, to nephron loss and progressively declined GFR [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%